Relevance of the Balance of Power Theory and Theory of Deterrence for Nepal’s National Security - Giri, Naresh (Unity Journal, 2025)
Fundamental objective of National security is state’s survival within an anarchic international system, where the lack of a world government and the sovereign status of states complicate the enforcement of a rule-based international order and compel states into a self-help situation. The Theory of Balance of Power suggests how states behave to bring the power balance in their favour, while the Theory of Deterrence aims to prevent attacks by deterring potential aggressors. Examination of these theories in relation to Nepal's security challenges is a critical research problem in this study. Understanding the Balance of Power theory is crucial in national security policy decisions, as it guides state behavior, while deterrence provides practical defence mechanisms. Even minor lapses can threaten state survival, underscoring the need for strategic understanding. The study aims to identify viable security options for Nepal by examining these theories’ relevance and application. Methodologically, the research uses a case study approach, relying on secondary sources like books and journals for data collection, which is primarily qualitative. This paper argues that with the global power balance shifting toward Asia, Nepal’s non-aligned stance remains pertinent. However, achieving minimum deterrence requires Nepal to modernize its military through cooperation with global powers and neighboring states. Additionally, developing indigenous military technology is crucial to strengthen Nepal's defence capabilities.